Prinsip Pelaksanaan Puasa Menurut Yoel 2: 12-17 Bagi Kekristenan Masa Kini - Esron Mangatas Siregar (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
This research is motivated by the existence of problems in Christianity that reject the implementation of fasting, differences in the concept of implementing fasting, a less firm basis in understanding fasting in the Christian concept, and wrong motives in carrying out fasting. Through qualitative research methods and descriptive analysis through literature studies, specifically the text of the Book of Joel 2:12-17. The results of the analysis show that Joel 2:12-17 calls for fasting with the first principle: following the word of God because God is merciful and merciful, God is long-suffering and abundant in faithfulness. Second, turn to God with all your heart, cry and moan. Third, tear the heart and Fourth humble yourself. Thus there is a restoration of the relationship between man and God and a focus on God's will, all of which straighten out the wrong practice of fasting.